Проблема автотеличности языка в романах Виктора Пелевина - Jaworski, Mateusz (Kultury Wschodniosłowiańskie – Oblicza i Dialog, 2018)
Viktor Pelevin is one of the most outstanding novelists in contemporary Russian literature. His works are popular with both professional critics and ordinary readers in the whole world. The present paper aims at finding the key characteristics of Pelevin’spoetics. Therefore, the author has decided to employ the notion of reconfiguration, which depicts the complexity of interrelations between the Russian writer’s novels. The conductedanalysis of one of the dominant aspects of this intertextual network — the motif of the autoteleology of language — has revealed a new universe of meanings.